Clinical features and risk factors for diabetic ketoacidosis in type 1 diabetes mellitus at tertiary care centre, Maharashtra, India - Gaikwad, Vijaykumar; Deshmukh, J. K.; Deshmukh, Prachi; Takalkar, Anant A. (International Journal of Advances in Medicine, 2020)
Background: Diabetes Mellitus is increasing in incidence, prevalence and importance as a chronic disease throughout the world. The International Diabetes Federation projects that by 2030 there will be 438 million people with diabetes on a global scale. Three essential components of Diabetic Ketoacidosis are hyperglycemia, ketosis, and resultant metabolic acidosis. 4% of all patients with diabetes and 20% of those with Type 1 Diabetes are admitted to hospital with manifestations of ketoacidosis. Objectives was to study clinical profile of patients presenting as Diabetic Ketoacidosis. Methods: It is a descriptive observational study was conducted at Department of Medicine, Dr. Shankarrao Chavan Medical College and Hospital, Nanded. The study included 77 patients of diabetic ketoacidosis (DKA) from Male Medicine ward, Female Medicine ward, Medical Intensive Care Unit. The study was carried out during Jan 2012 to October 2013. The data was analyzed using SPSS 24.0 version. Results: Majority of the subjects were from 10-20 years age group i.e. 31(40.3%). 51.9% were males and 42.9% were females. 38(49.4%) have onset of Diabetes type 1 between 10- 20 years of age and mean±S.D.20.11±7.09yrs. Most common symptoms at the time of admission were abdominal pain in 54(70.1%), vomiting in 52(67.5%), nausea in 41(53.2%) and fatigue in 40(51.9%) patients. Most common risk factor for DKA was found to be infections in 36(46.8%) patients. Conclusions: Most common clinical features of Diabetic Ketoacidosis were abdominal pain, vomiting, nausea and fatigue. Most common risk factor for Diabetic Ketoacidosis was infection followed by omission of treatment or irregular treatment. The most common infections were due to urinary tract & respiratory tract infections.